O6A.4 Risk of postmenopausal breast cancer and occupational exposure to chemicals in swedish women. (April 2019) - Gustavsson, Per; Videnros, Cecilia; Wiebert, Pernilla; Plato, Nils; Borgquist, Signe; Manjer, Jonas; Albin, Maria; Selander, Jenny
Abstract : Earlier studies have led to a hypothesis of an increased risk of breast cancer after exposure to organic solvents. This study aimed to investigate if exposure to various chemicals in the workplace was associated with an increased risk of breast cancer. The study comprised 14 119 women born 1923–1950 and living in Malmö city, Sweden, who were enrolled for a prospective population cohort study between 1991 and 1996. Oc cupational exposure to various chemicals was assessed from a job-exposure matrix. Individual data on other breast cancer risk factors (age, parity, age at first pregnancy, breastfeeding, hormonal replacement therapy, physical activity, alcohol consumption, height and BMI) were collected at baseline and used for confounding control. Diagnoses of invasive breast cancer were obtained from the Swedish Cancer Registry until end of follow-up at 2013–12–31. Women exposed to any type of chemical (organic solvents, pesticides, fumes or oil mist) for more than 10 years (66 cases) showed an increased adjusted breast cancer risk, HR=1.43, (95% CI 1.10–1.85), and the risk correlated positively with duration of exposure. Investigation of risk in association with organic solvents showed a small and non-significantly elevated risk after >10 years of exposure, HR=1.18 (95% CI 0.81–1.71). The risk tended to be higher, but not significantly elevated, after >10 year of exposure than after 1–10 years of exposure for most of the studied chemicals. More than 10 years of exposure to diesel exhaust was associated with an increased risk (adjusted HR=1.69, 95% CI 1.01–2.82). Occupational exposure to chemicals in general was associated with an elevated risk of postmenopausal breast cancer, but the study gives no firm support for the hypothesis of an association with exposure to organic solvents. An elevated risk after >10 years of exposure to diesel exhaust was an unexpected finding that needs to be investigated further.